Axial Ligand Coordination Tuning of the Electrocatalytic Activity of Iron Porphyrin Electrografted onto Carbon Nanotubes for the Oxygen Reduction Reaction. Issue 38 (26th May 2021) - Zhou, Xin‐You; Xu, Chao; Guo, Peng‐Peng; Sun, Wei‐Li; Wei, Ping‐Jie; Liu, Jin‐Gang
Abstract: The oxygen reduction reaction (ORR) is essential in many life processes and energy conversion systems. It is desirable to design transition metal molecular catalysts inspired by enzymatic oxygen activation/reduction processes as an alternative to noble‐metal‐Pt‐based ORR electrocatalysts, especially in view point of fuel cell commercialization. We have fabricated bio‐inspired molecular catalysts electrografted onto multiwalled carbon nanotubes (MWCNTs) in which 5, 10, 15, 20‐tetra(pentafluorophenyl) iron porphyrin (iron porphyrin FeF20 TPP) is coordinated with covalently electrografted axial ligands varying from thiophene to imidazole on the MWCNTs' surface. The catalysts' electrocatalytic activity varied with the axial coordination environment (i. e., S ‐thiophene, N ‐imidazole, and O ‐carboxylate); the imidazole‐coordinated catalyst MWCNTs‐Im‐FeF20 TPP exhibited the highest ORR activity among the prepared catalysts. When MWCNT‐Im‐FeF20 TPP was loaded onto the cathode of a zinc−air battery, an open‐cell voltage (OCV) of 1.35 V and a maximum power density ( P max ) of 110 mW cm −2 were achieved; this was higher than those of MWCNTs‐Thi‐FeF20 TPP (OCV=1.30 V, P max =100 mW cm −2 ) and MWCNTs‐Ox‐FeF20 TPP (OCV=1.28 V, P max =86 mW cm −2 ) and comparable with a commercial Pt/C catalyst (OCV=1.45 V, P max =120 mW cm −2 ) under similar experimental conditions. This study provides a time‐saving method to prepare covalently immobilized molecular electrocatalysts on carbon‐based materials with structure–performance correlation that is also applicable to the design of other electrografted catalysts for energy conversion. Abstract : A time‐saving electrografting method (within a couple of minutes) for the covalent functionalization of carbon nanotube surfaces with an imidazole or thiophene ligand that is axially coordinated with iron porphyrin as electrocatalyst for the oxygen reduction reaction (ORR) has been demonstrated. The N ‐imidazole‐coordinated catalyst, MWCNT‐Im‐FeF20 TPP, exhibited the highest ORR activity followed by the S ‐thiophene and O ‐carboxylate axially coordinated catalysts.